Um modelo para avaliação de usabilidade em um cenário de convergência digital - Kronbauer, Artur Henrique; Santos, Celso A. S. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2011: Proceedings of the 17th Brazilian Symposium on Multimedia and the Web, 2011)
Converging devices, such as cell phones and Interactive Digital TV, are on the list of the most sold equipment nowadays. Besides the great search for those equipment, the diversity of users, differences on the form of interaction, dimension of equipment, aspects of mobility and diversified use scenarios, demand usability assessments for the investigation of possible improvement of the interaction involving users and the interfaces of the available applications. In this paper we present a model to evaluate the usability of applications for this kind of device. The proposed model is divided in three modules: (i) mapping of the intensions of the application’s designer, (ii) capture of the user’s interactions with the application’s interface, (iii) module of comparison between the intentions of the designer and the usability of the final user.